Enhancing offspring hypothalamic-pituitary-adrenal (HPA) regulation via systematic novelty exposure: the influence of maternal HPA function - Dinces, Sarah M.; Romeo, Russell D.; McEwen, Bruce S.; Tang, Akaysha C. (Frontiers in Behavioral Neuroscience, 2014)
In the rat, repeated brief exposures to novelty early in life can induce long-lasting enhancements in adult cognitive, social, emotional, and neuroendocrine function. Family-to-family variations in these intervention effects on adult offspring are predicted by the mother’s ability to mount a rapid corticosterone (CORT) response to the onset of an acute stressor. Here, in Long-Evans rats, we investigated whether neonatal and adulthood novelty exposure, each individually and in combination, can enhance offspring HPA regulation. Using a 2x2 within-litter design, one half of each litter were exposed to a relatively novel non-home environment for 3-min (Neo_Novel) daily during infancy (PND1-21) and the other half of the litter remained in the home cage (Neo_Home); we further exposed half of these two groups to early adulthood (PND54-63) novelty exposure in an open field and the remaining siblings stayed in their home cages. Two aspects of HPA regulation were assessed: the ability to maintain a low level of resting CORT (CORTB) and the ability to mount a large rapid CORT response (CORTE) to the onset of an acute stressor. Assessment of adult offspring’s ability to regulate HPA regulation began at 370 days of age. We further investigated whether the novelty exposure effects on offspring HPA regulation are sensitive to the context of maternal HPA regulation by assessing maternal HPA regulation similarly beginning 7 days after her pups were weaned. We found that at the population level, rats receiving neonatal, but not early adulthood exposure or both, showed a greater rapid CORTE than their home-staying siblings. At the individual family level, these novelty effects are positively associated with maternal CORTE. These results suggest that early experience of novelty can enhance the offspring’s ability to mount a rapid response to environmental challenge and the success of such early life intervention is critically dependent upon the context of maternal HPA regulation.